Dynamics of development motive capabilities, psychophysiological and functional possibilities of boys 4-6 years - Gavrishko S.G (Kharkov National Pedagogical University, 2010)
The problem of determination of level of development motive capabilities is examined. Directions of prognostication inclination of children of early age are rotined to the certain type of motive activity. The complex testing of individual possibilities of boys is conducted 4-6 years. Comparative description of indexes of motive function is presented during six testing. Certain the loud speaker of development of motive capabilities, psychophysiological and functional possibilities of boys. The general tendencies of change of these indexes are exposed during three years.